Enhancing water stress tolerance of bread wheat during seed germination and seedling emergence: caffeine-induced modulation of antioxidative defense mechanisms - Ali, Qasim; Perveen, Rashida; Saeed, Farah; Manzoor, Hunaina; Ali, Shafaqat; Hussain, Muhammad Iftikhar; Ahmad, Ajaz (Frontiers in Plant Science, 2024)
Better crop stand establishment, a function of rapid and uniform seedling emergence, depends on the activities of germination-related enzymes, which is problematic when there is insufficient soil moisture. Different ways are in practice for counteracting this problem, including the seed priming with different chemicals, which are considered helpful in getting better crop stand establishment to some extent through improved seed germination and seedling emergence. In this growth room experiment, caffeine was used as a seed priming agent to improve germination under moisture scarcity. Polyethylene glycol-8000 (18%) was added in Hoagland’s nutrient solution to create drought stress (-0.65 M.Pa). The experiment was arranged in CRD, having four replications of each treatment. Newly developed wheat genotype SB-1 was used for the experimentation. Different doses of caffeine i.e. 4, 8, 12 and 16 ppm, including no soaking and water soaking, were used as seed priming treatments. Water deficit caused oxidative stress and adversely affected the seed germination, seedling vigor, activities of germination enzymes, photosynthetic pigments and antioxidative defense mechanism in roots and shoots of seedlings. Caffeine seed priming ameliorated the negative effects of water deficit on seed germination and seedling vigor, which was attributed to the reduction in lipid peroxidation and improvement in activities of germination-related enzymes like glucosidase, amylase and protease. Conclusively, seed priming with 12 ppm caffeine outperformed the other treatments and hence recommended for better crop stand establishment under conditions of soil moisture deficit.